Principles of biochemistry - Voet, Donald; Voet, Donald; Voet, Judith G.; Pratt, Charlotte W. (Singapore, John Wiley, 2016)
Voet$1 (Bs Principles of Biochemistry, Global Edition addresses the enormous advances in biochemistry, particularly in the areas of structural biology and bioinformatics. It provides a solid biochemical foundation that is rooted in chemistry to prepare students for the scientific challenges of the future. New information related to advances in biochemistry and experimental approaches for studying complex systems are introduced. Notes on a variety of human diseases and pharmacological effectors have been expanded to reflect recent research findings. While continuing in its tradition of presenting complete and balanced coverage, this Global Edition includes new pedagogy and enhanced visuals that provide a clear pathway for student learning.s
Keywords: Biomolecules; Enzymes; Life cell and thermodynamics; Metabolism; Zoology